Learning-centred parental engagement: Freire reimagined. Issue 5 (20th October 2018) - Goodall, Janet
Abstract: This article builds on the seminal work of Paulo Freire, whose critique of the "banking model" of education has inspired educators to look beyond mechanistic, didactic means of teaching, toward more constructivist, engaging methods. In this article, I argue that, although the teaching of children has changed as a result of work such as Freire's, school staff often revert to a "banking model" when seeking to engage parents. This paper utilises Freire's characteristics of "banking education" as a lens to look at relationships between schools and families. Based on this, the paper then suggests a way of moving toward a more equitable, sustainable and fruitful partnership between all those involved in schooling and learning (with the former being a formalised subset of the much larger latter).